Challenges in Sustaining a Peripheral Journal (2018)
We have reviewed the characteristics of Profile to try and decide whether it is a mainstream or a peripheral journal. We have analysed the parameters under which it operates and we can say that these correspond to a high-quality journal, a journal from the periphery that is putting forth its best effort to produce science that is validated by local and international communities.